Assessment of methods for hemoglobin determination recommended for field use - Santiago, Ma. Isabel Z. Cabrera
The performance of the cyanmethemoglobin method on a portable spectrophotometer (B&L Mini 20), the oxyhemoglobin method on a portable calorimeter (AO Hb Meter), and the filter paper method, a modification of the cyanmethemoglobin method was assessed in terms of reproducibility and accuracy relative to the reference method. Cyanomethemoglobin determination on a B&L Spectronic 70 was the reference method. Within-the-day reproducibility of quadruplicate hemoglobin determination from a singe finger prick on the same subject, between-days reproducibility of hemoglobin measurements on the same subject at intervals of four days +- one day, and accuracy relative to reference value were determined. The accuracy of the filter paper method was assessed in terms of the stability of hemoglobin concentration in blood dried on filter paper at zero, five, ten and fifteen days after blood had been spotted on the paper. Hemoglobin values obtained within the B&L Mini 20 were reproducible and accurate relative to reference method. Results with the AO Hb Meter were not reproducible and values obtained were significantly higher that the reference values. Hemoglobin results of filter paper specimens analyzed within the same day blood was spotted were reproducible. Hemoglobin concentration in filter paper specimens analyzed after five days was comparable, while those analyzed after 10 and 15 days were significantly lower than those analyzed on the same day blood was spotted. Corresponding reference hemoglobin values were 13 percent higher than those obtained in filter paper specimens analyzed on the same day.